Hukuman Bagi Ayah yang Tidak Menafkahi Anak Kandungnya dalam Perspektif Hadis HR. Ibnu Majah dan Pasal 77 UU No. 23 Tahun 2022 - Nabila Rahmadani; Tajul Arifin (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
The role of fathers in children's lives cannot actually be underestimated. Unfortunately, there are still many children in Indonesia who grow up without the presence or maximum role of a father. This phenomenon is known as fatherlessness. Either because the father is not there (due to divorce or death), or because the father is there but does not carry out his role well. In fact, according to Islamic teachings and legal regulations in Indonesia, fathers have a big responsibility to provide for their children, both materially, with love and attention. Through this study, it is discussed how Islam provides strong warnings for negligent fathers, even calling it a major sin. The Prophet's hadith also emphasizes a lot about a father's responsibility towards his family. Not only that, Indonesian law also has clear regulations regarding sanctions for fathers who abandon their children, including criminal threats. In essence, fathers are not only breadwinners, but also important figures in children's growth and development. If this role is ignored, the impact could be big for the child, family, and even the future of the father himself. The state and society must care more about this, so that Indonesian children can grow up healthy, complete and happy.